(3JGQjN CHj HTQ gGQhf Hf MGJe GdHRGRs - (3Gdchaj, CHh HTQ, GdHRGR, gGQhf Hf MGJe, J (B249 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B...(3bQCJ Ydi GdTjN GdEeGe CHj GdbGSe ESeGYjd Hf eMeO Hf YeQ Hf GdSeQbfOj CjOg Gddg HHZOGO bdJ dg CNHQce GdbGVj CHh GdaJM fUQ Hf GMeO Hf fUQ GdNWjH GdSefLGfj(B...s
(3BNQgG (B:s
..... (3hcGf GSe CHj CShO GdOQdj XGde Hf YeQh Hf SajGf hcGf GSe CHj HQRI (B.. (3YeQh Hf YGeQ Hf Hf YHO Gddg (B...(3hGdMeO ddgs
(3JHUQI GdYfhGf (B:s
(3eYLe GdeDdajf (B4 \ 49s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8\60s
(3GdJGQjNs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs